First Photo-Identification Study of the Sperm Whale (Physeter macrocephalus) in the Aeolian Archipelago and the Northern Coast of Sicily (Southern Tyrrhenian Sea, Italy) - Agata Irene Di Paola; Michelle Gelippi; Monica Francesca Blasi (Diversity)
(1) While photo-identification has been used to study sperm whales worldwide, no long-term photo-id studies are available from the Southern Tyrrhenian Sea for the Mediterranean endangered population. (2) Here, sperm whale occurrence, group size, and the type of encounters were investigated around the Aeolian archipelago (Southern Italy) by photo-ID data collected between 2013 and 2024. Data were obtained through dedicated boat surveys and recreational sailors’ reports. (3) During 58 sighting events, 125 sperm whales were encountered, 60 of whom were photo-identified and cataloged. Of these, two sperm whales were found entangled. Only five individuals were re-sighted in later years or seasons. Encounters were more frequent in autumn, consisting mainly of solitary individuals (53.4%, n = 31) and aggregations of clustered, often not sexed, animals (23.5%, n = 8). Social units of females and calves were also encountered (8.6%, n = 5). (4) The low site fidelity and the group types encountered suggest that dispersed young males and social groups could use the area simultaneously. (4) Future matching of these data with databases from other surveyed areas, acoustic surveys, and enhanced analysis of age classes are crucial to better define the ecological role of the study area for the Mediterranean sperm whale population.